Drug discovery at the site of pulmonary tuberculosis - Tanner, Lloyd (Department of Medicine, 2019)
The protracted duration of standard tuberculosis (TB) therapy suggests the inadequacy of current first line TB drugs to eliminate the causative agent Mycobacterium tuberculosis (Mtb). Among multiple potential causes, this may be due to poor distribution of TB drugs into the pulmonary lesions in which the bacilli reside. In attempting to explore this possibility, the study described here aimed to assess selected novel compounds (phenoxazine, artemisinin, and decoquinate derivatives) proposed to induce redox-cycling in efficacious combinations, as well as their distribution to TB-relevant lesions, for potential clinical use against TB. To this end, specific in vitro absorption, distribution, metabolism, and excretion (ADME) assays were performed to predict the abilities of the compounds to penetrate different TB microenvironments. Penetration into murine blood and organs was assessed via pharmacokinetic (PK) profiling. Complementary analyses involving murine epithelial lining fluid allowed for more detailed analyses of the potential of these novel compounds to penetrate the deeper recesses of the lung. In order to gain a greater understanding of the potential efficacy of the compounds in an intracellular environment, THP-1 macrophage-like cells were infected with Mtb, treated with anti-TB agents, and sampled at different time-points. Samples were analyzed via liquid chromatography-tandem mass spectrometry (LC-MS/MS) assays and drug concentrations were determined and related to efficacy measurements using colony forming unit counts. Promising combinations of novel drugs were identified in a two dimensional synergy assay; these combinations showed synergistic activity in the infected macrophage model. The compounds showed marked differences in their abilities to accumulate within infected macrophages. Differential uptake was also indicated by the results of the PK studies involving murine blood and organ uptake, and the in vitro ADME assays. These results enable PK modelling on the putative drug target to be carried out, allowing for the determination of more accurate dosing. In addition, results indicate the need for further studies, including investigations of the impact of macrophage structural organisation (three-dimensional model) on compound efficacy and in vivo studies in a relevant mouse model of TB disease. The identification of a potentially efficacious two drug combination which might penetrate to the site of pulmonary TB supports the utility of this approach in the preclinical drug discovery and development pipeline.